2019
DOI: 10.1002/jgh3.12175
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic esophagitis: An Australian (Queensland) case series of a newly recognized mimic of eosinophilic esophagitis

Abstract: Background and Aim Lymphocytic esophagitis (LoE) is a recently described upper gastrointestinal tract “disorder” diagnosis of which hinges on histology and is characterized by the excessive infiltration of lymphocytes in the peripapillary fields of the esophageal epithelium, with clinical manifestations similar to those of eosinophilic esophagitis (EoE). In this article, we aim to describe for the first time the clinico‐pathological characteristics of a large cohort of Australian (Queensland) cases of LoE. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…У пациентов также может возникать острое вклинение пищи в пищевод [39] -состояние, которое наиболее часто выявляется при ЭоЭ. Не только клиническая картина, но и эндоскопические признаки лимфоцитарного эзофагита во многом сходны с таковыми при ЭоЭ [39][40][41][42]. В то же время пациенты с ЭоЭ обычно моложе, и при лимфоцитарном эзофагите отмечается преобладание женщин [43].…”
Section: лимфоцитарный эзофагитunclassified
“…У пациентов также может возникать острое вклинение пищи в пищевод [39] -состояние, которое наиболее часто выявляется при ЭоЭ. Не только клиническая картина, но и эндоскопические признаки лимфоцитарного эзофагита во многом сходны с таковыми при ЭоЭ [39][40][41][42]. В то же время пациенты с ЭоЭ обычно моложе, и при лимфоцитарном эзофагите отмечается преобладание женщин [43].…”
Section: лимфоцитарный эзофагитunclassified
“…The most common presenting symptom in all studies is dysphagia, followed by reflux or heartburn, abdominal or chest pain, nausea and/or vomiting and odynophagia. [58][59][60][61][62][63][64] A number of studies have indicated that, relative to those with a normal oesophagus or other forms of oesophagitis, reflux-type symptoms are half as common in those with LO. 59,62 Phlebitis and plexitis, 1/6…”
Section: L I N I C a L F E A T U R E Smentioning
confidence: 99%
“…65 Numerous studies in adult patients have failed to support a significant association with chronic inflammatory bowel disease. 57,59,[61][62][63]65 Associations with Helicobacter pylori gastritis, 62 lichen planus 66 and hypothyroidism 58 have also been described.…”
Section: L I N I C a L F E A T U R E Smentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, other esophageal diseases such as lymphocytic esophagitis share the endoscopic findings of EoE (eg, rings, strictures, furrows) even in 47% of cases. 8 Indeed, these esophageal changes have shown variable positive and negative predictive values for the diagnosis of EoE; therefore, biopsies are mandatory for EoE diagnosis. Response:…”
Section: Concomitant Esophageal Intramural Pseudodiverticulosis and Ementioning
confidence: 99%